2003
DOI: 10.1111/j.1651-2227.2003.tb00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐discharge nutrition of the very low‐birthweight infant: interim results of the multicentric GAMMA study

Abstract: This report presents the interim results up to 12 mo corrected age (c.a.) of a multicentric, prospective, controlled study on very low‐birthweight infants, randomized at 40 wk post‐conception in two different groups of formula feeding: 80 Kcal/dL (group A) vs 70 Kcal/dL (group B) up to 55 wk of postconceptional age. Subsequently, all the babies were fed with a follow‐on formula, with the introduction of solid foods at 6 mo c.a. Weight, length, head circumference and neurological conditions with psychomotor dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
(18 reference statements)
0
25
0
Order By: Relevance
“…In total, we identified 16 trials that fulfil review eligibility criteria (Agosti 2003;Atkinson 1999;Atkinson 2004;Carver 2001;Cooke 2001;De Curtis 2002;Jeon 2011;Koo 2006;Litmanovitz 2004;Lucas 1992;Lucas 2001;Peng 2004;Picaud 2005;Roggero 2011;Roggero 2012;Taroni 2009). See Characteristics of included studies.…”
Section: Included Studiesmentioning
confidence: 99%
“…In total, we identified 16 trials that fulfil review eligibility criteria (Agosti 2003;Atkinson 1999;Atkinson 2004;Carver 2001;Cooke 2001;De Curtis 2002;Jeon 2011;Koo 2006;Litmanovitz 2004;Lucas 1992;Lucas 2001;Peng 2004;Picaud 2005;Roggero 2011;Roggero 2012;Taroni 2009). See Characteristics of included studies.…”
Section: Included Studiesmentioning
confidence: 99%
“…Indeed, to our knowledge, studies investigating the effect on neurodevelopmental outcome of high protein and energy intake after hospital discharge in preterm infants, who are randomized and evaluated separately according to intrauterine growth pattern, are scarce. Agosti et al [6] reported interim results from a multi-center, randomized controlled study on 121 very low-birth weight infants. Infants were randomized at term corrected age to receive either a preterm formula (2.4 g/100 ml and 80 kcal/100 ml) or a standard term formula (1.7 g/100 ml and 70 kcal/100 ml) up until 55 weeks of corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are reported following the CONSORT guidelines. Details of the study are reported elsewhere [6]. The trial was registered with Current Controlled Trials (http://www.controlled-trials.com/ISRCTN30189842) London, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three trials have examined growth in preterm infants fed with ‘preterm formula’ versus standard term formula milk for 4–6 months following hospital discharge 3234. These trials found inconsistent effects on weight gain and no significant differences in length and head circumference at 12–18 months post-term.…”
Section: Preterm Formula Versus Term Formulamentioning
confidence: 99%